1994
DOI: 10.1093/nar/22.7.1147
|View full text |Cite
|
Sign up to set email alerts
|

The BCMA gene, preferentially expressed during B lymphoid maturation, is bidirectionally transcribed

Abstract: In a previous study of a t(4;16)(q26;p13) translocation, found in a human malignant T-cell lymphoma the BCMA gene, located on chromosome band 16p13.1, has been characterized. In this study we show that the BCMA gene is organized into three exons and its major initiation transcription site is located 69 nucleotides downstream of a TATA box. RNase protection assays demonstrated that the BCMA gene is preferentially expressed in mature B cells, suggesting a role for this gene in the B-cell developmental process. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(145 citation statements)
references
References 62 publications
5
140
0
Order By: Relevance
“…In patients treated more than once, similar rises in serum BLyS levels occurred following each course of BCDT (Figure 2). Because the expression of BLyS receptors is largely restricted to B cells (4,(33)(34)(35)(36)(37), the increase in serum BLyS levels following BCDT may be attributable, at least in part, to the physical loss of BLyS-binding B cells (26). Alternatively, BLyS production may be under homeostatic control from an as-yet-unidentified negative feedback signal from the B cell compartment that is deficient during periods of B cell depletion.…”
Section: Discussionmentioning
confidence: 99%
“…In patients treated more than once, similar rises in serum BLyS levels occurred following each course of BCDT (Figure 2). Because the expression of BLyS receptors is largely restricted to B cells (4,(33)(34)(35)(36)(37), the increase in serum BLyS levels following BCDT may be attributable, at least in part, to the physical loss of BLyS-binding B cells (26). Alternatively, BLyS production may be under homeostatic control from an as-yet-unidentified negative feedback signal from the B cell compartment that is deficient during periods of B cell depletion.…”
Section: Discussionmentioning
confidence: 99%
“…23,26,27 Using RT-PCR, the presence of TACI and BAFF-R mRNAs was found in nearly all leukemic B cells (7 of 9 patients for TACI, 9 of 9 patients for BAFF-R) and in blood-derived normal B cells (5 of 5 donors) (Figure 1), in agreement with the findings of Novak et al 45 The latter showed, in addition, that BCMA mRNA was detected in a subset of B-CLL patients. Moreover, by flow cytometry, they found significant levels of TACI protein at the surfaces of these cells; the lack of suitable antibodies made it difficult to check the membrane expression of BCMA and BAFF-R. 45 These results indicated that leukemic B cells expressed at their surfaces the 2 receptors for BAFF and APRIL.…”
Section: Expression Of Taci and Baff-r Mrnas In Normal B Lymphocytes mentioning
confidence: 99%
“…22 BAFF, but not APRIL, binds a third receptor named BAFF receptor (BAFF-R or BR3). [23][24][25] BCMA, TACI, and BAFF-R are expressed on normal B lymphocytes 23,26,27 and on a subset of activated T cells for TACI. 27 This system of receptors/ligands is a key factor for B-cell survival and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…11 BLyS and a proliferation-inducing ligand (APRIL) bind to B cell maturation antigen (BCMA) and transmembrane activator and CAML-interactor (TACI), 4,12,13 which belong to the tumor necrosis factor receptor superfamily and are mainly expressed in B cells. [14][15][16][17] The intracellular domains of BCMA and TACI associate with TNFreceptor-associated factors (TRAFs), leading to activation of NF-kB. 18,19 Recently, another receptor for BLyS, BAFF-R (also called BR3) was identified, which does not bind to APRIL.…”
Section: Introductionmentioning
confidence: 99%